Effect of strain on gas‐phase basicity of (E)‐1‐methyl‐2‐(1‐methyl‐2‐adamantylidene)adamantane. (27th March 2015) - Kekišev, Ott; Kaljurand, Ivari; Toom, Lauri; Lenoir, Dieter; Burk, Peeter; Järv, Jaak
<x xml:space="preserve">Abstract</x> Steric strain, caused by forced deformation of double bond geometry, has significant impact on alkene reactivity, as was shown by a study of the gas‐phase basicity of (E)‐1‐methyl‐2‐(1‐methyl‐2‐adamantylidene)adamantane. The Gibbs free energy of the strain effect in this compound was 42 kJ/mol. This analysis was made based on adamantylideneadamantane as a congeneric reference compound with a planar double bond. It was concluded that gas‐phase basicity could serve as a valuable alternative indicator for quantification of steric strain in alkenes. Copyright © 2015 John Wiley & Sons, Ltd.